Two KCNQ2 Encephalopathy Variants in the Calmodulin-Binding Helix A Exhibit Dominant-Negative Effects and Altered PIP2 Interaction - Tran, Baouyen; Ji, Zhi-Gang; Xu, Mingxuan; Tsuchida, Tammy N.; Cooper, Edward C. (Frontiers in Physiology, 2020)
Heterozygous missense variants in KCNQ2, which encodes the potassium channel subunit Kv7.2, are among the most common genetic causes of severe neonatal-onset epileptic encephalopathy. Because about 20% of known severe Kv7.2 missense changes lie within the intracellular C-terminal region, improving understanding of the underlying pathogenic mechanisms is important. We analyzed the basis for the severe phenotypes of Kv7.2 A337T and A337G, variants in the C-terminal’s proximal calmodulin (CaM)-binding Helix A. When expressed heterologously in mammalian cells, alone or in combination with wild type Kv7.2 or with wild type Kv7.2 and Kv7.3, both variants strongly suppressed channel currents. A337T channels expressed alone exhibited significantly reduced protein half-life, and lower surface trafficking, and co-immunoprecipitated less CaM. For both variants, increasing cellular phosphatidylinositol 4,5-bisphosphate (PIP2) by overexpression of PI(4)P5-kinase restored current densities. For both variants, the fraction of current suppressed by activation of M1 muscarinic receptors with 10 M oxotremorine methiodide, which depletes PIP2, was less than for controls. During voltage-sensitive phosphatase-induced transient PIP2 depletion and resynthesis, potassium current inhibition and recovery kinetics were both markedly slowed. These results suggest that these variants may reduce currents by slowing migration of PIP2 between the bulk membrane and binding sites mediating channel electromechanical coupling. A novel Kv7-selective opener, SF0034, rescued current amplitudes. Our findings show that these two Helix A variants suppress channel current density strongly, consistent with their severe heterozygous phenotypes, implicate impairment of CaM and PIP2 regulation in KCNQ2 encephalopathy pathogenesis, and highlight the potential usefulness of selective Kv7 openers for this distinctive pathogenic mechanism and patient subgroup.